2012
DOI: 10.1039/c1cp22824b
|View full text |Cite
|
Sign up to set email alerts
|

Explaining statin inhibition effectiveness of HMG-CoA reductase by quantum biochemistry computations

Abstract: By taking advantage of the crystallographic data of 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) complexed with statins, a quantum biochemistry study based on the density functional theory is performed to estimate the interaction energy for each statin when one considers binding pockets of different sizes. Assuming a correlation between statin potency and the strength of the total HMGR-statin binding energy, clinical data as well as IC(50) values of these cholesterol-lowering drugs are successfully e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 29 publications
3
68
0
1
Order By: Relevance
“…In our study, simvastatin, a highly lipophilic statin, demonstrated less protective effects than atorvastatin, a lesser lipophilic statin. Pharmacologically speaking, atorvastatin is much more potent than simvastatin, with stronger binding capacity to HMG-CoA inhibitors (da Costa et al , 2012), which may explain the better outcomes in our H-statin group, in which the majority of patients were using atorvastatin.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, simvastatin, a highly lipophilic statin, demonstrated less protective effects than atorvastatin, a lesser lipophilic statin. Pharmacologically speaking, atorvastatin is much more potent than simvastatin, with stronger binding capacity to HMG-CoA inhibitors (da Costa et al , 2012), which may explain the better outcomes in our H-statin group, in which the majority of patients were using atorvastatin.…”
Section: Discussionmentioning
confidence: 94%
“…The conformational flexibility has sterically hindered the substrate from binding with the enzyme. Concurrently, the statin structure extends into the narrow pantothenic acid-binding pocket moiety of coenzyme A which eventually blocks the coenzyme A of the substrate [11, 12]. This is why statins are capable of competing with the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…10,35 Experimental, computational and crystallographic analysis has been used to describe partial agonism by 5-substituted willardiines in AMPA receptors. The analysis of crystallographic structures can be done based on important methods, such as virtual screening of the distances and sizes of connections, the de novo design, molecular docking and molecular dynamics, 37,38 which are limited by the lack of information on the interaction between specific residues of the receptor and the different ligands, which would be quite useful for the design of new drugs. The analysis of crystallographic structures can be done based on important methods, such as virtual screening of the distances and sizes of connections, the de novo design, molecular docking and molecular dynamics, 37,38 which are limited by the lack of information on the interaction between specific residues of the receptor and the different ligands, which would be quite useful for the design of new drugs.…”
Section: Introductionmentioning
confidence: 99%